IMPLEMENTASI PENGELOLAAN PESERTA DIDIK DALAM MENJAMIN MUTU LULUSAN TAMAN PENDIDIKAN AL-QUR’AN HIDAYATUR ROHMAN LAMPUNG SELATAN - Cahyo, Ahmad (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2024)
In ensuring the quality of student graduates, there are several efforts made by TPQ Hidayatur Rohman South Lampung in terms of administrative analysis of student needs, recruitment, selection, academic and non-academic activity programs. system of admission and selection, orientation, regulating attendance and absence. There are several efforts made to ensure the quality of graduates, namely discipline, example, student achievement cards, rewards and punishments, optimizing the role of leaders, preparing professional educators, fostering qualifications and improving teacher competence, improving public relations, increasing class hours for those who will take the final exam, guiding outstanding students, praying for students, holding learning programs for TPQ graduates. The supporting and management factors in ensuring the quality of graduates come from teachers, high student will, and parental support. Meanwhile, the inhibiting factors are the recitation schedule that clashes with the school schedule, the lack of learning spaces, inadequate facilities and infrastructure, and the lack of financing as one of the biggest inhibiting factors in ensuring the quality of graduates, for example, the incentive for TPQ teachers which is still relatively minimal, the cost of electricity increases, so that income and expenditure are unbalanced.